PENERIMAAN INFORMASI PADA APLIKASI INSTAGRAM SAAT STAY AT HOME DAN WORK FROM HOME - Syatantra Rahutama; Imam Himawan (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The number of active Instagram application users every day reaches more than 500 million, and Instagram application users who upload almost 500 million more stories every day. So the flow of information shared by one user to another user is very much, and when the CORVID 19 outbreak struck in various countries, users were presented with information in realtime on the Instagram application. So when the government implies that people are only at home, users of the Instagram application can still receive information. Instagram application users can access information and also get entertainment from the application above 50%, to measure the attitude of receiving information from users of the Instagram application on smart phones using the Technology Acceptance Model (TAM) and by using the variable ease, usefulness and attitude. The results of the analysis of these three variables are that from conveniences such as making posts and also uploading photos to stories and feeds have not been felt by some users which are indicated by the value of 0.40 on Easy  Attitude, e1  e13, namely external factors. But overall users take advantage of receiving information through the Instagram application.